Oxidative stress physiology in Scylla serrata for environmental health assessment - Pati, Samar Gourav; Panda, Falguni; Paital, Biswaranjan; Sahoo, Dipak Kumar; Jena, Srikanta (Frontiers in Environmental Science, 2023)
The oxidative stress (OS) condition and antioxidant level as a function of pH, few major elements, temperature, turbidity, organic carbon, and sediment and water salinity are vital to understanding the redox homeostasis of inhabiting animals. These parameters are also used to monitor environmental health. A spatiotemporal redox antioxidant system followed by discriminant function analysis about the above abiotic factors was investigated in muscle, gill, and hepatopancreas of mud crab, Scylla serrata, sampled from the Indian coastal belt along the Bay of Bengal (Tamil Nadu and Odisha) and the Arabian Sea (Gujurat) as a measure of environmental health assessment. Results revealed that redox homeostasis of mud crabs was significantly varied with seasonal fluctuation of abiotic factors and sediment chemistry. The level of superoxide dismutase and non-protein-SH group were negatively correlated, whereas other antioxidant molecules with lipid peroxidation levels were positively correlated with abiotic factors. Activities of only glutathione peroxidase and glutathione reductase were strongly correlated with all the abiotic factors. The hepatopancreas was found to be the most susceptible organ to OS. The lipid peroxidation level was 20 to 25 times higher in hepatopancreas tissue than in other tissues. The antioxidant level was elevated to 200% during the summer compared to the rainy season. Thus, the results of redox homeostasis in S. serrata may be useful for monitoring the ecotoxic effects of estuarine and marine environments and managing the inhabiting species.